Factors influencing sexual behaviors among youths in Myanmar: the results from the Myanmar demographic and health survey 2015–16 - Hlaing, Yoon Shwe Yee; Siewchaisakul, Pallop; Chautrakarn, Sineenart (Frontiers in Reproductive Health, 2025)
BackgroundYouths in Myanmar face heightened risks for adverse sexual health outcomes such as unintended pregnancies and sexually transmitted infections (STIs), including HIV/AIDS. Despite the increasing youth population in Myanmar, nationally representative data on factors influencing their sexual behaviors are limited. This study aimed to investigate the factors associated with sexual behaviors among youths in Myanmar.MethodsThis study used data from the Myanmar Demographic Health Survey 2015–16 to analyze a sample of 4,645 youths aged 15–24. Descriptive statistics were used to investigate sociodemographic factors, HIV/STI and contraceptive knowledge, and sexual behaviors. Multivariable logistic regression was used to identify factors associated with sexual behaviors. Adjusted odds ratios (AOR) and 95% confidence intervals (CI) were presented. Statistical significance was determined at a p-value of <0.05.ResultsAmong sexually active youths (n = 1,366), 47.0% reported having their first sex at or before the age of 18, 54.0% were currently using contraception, and only 8.1% of males had paid for sex. Higher education levels, middle, richer, and richest wealth, as well as moderate and high contraception knowledge, were all protective against early sexual initiation. Females and currently married youths were more likely to use contraception, while regional disparities persisted, with youths from hilly, coastal, and plains regions less likely to use contraceptives than those from the delta and lowlands. Married males were less likely to pay for sex. Male youths with moderate or high contraception knowledge reported higher risk of paying for sex.ConclusionAccording to this study, gender, education level, wealth status, marital status, region, and contraceptive knowledge all have a significant impact on sexual behaviors among Myanmar youths. Early sexual initiation and low contraceptive use are common, especially among young people with low education and socioeconomic status. Targeted, inclusive, and culturally sensitive sexual and reproductive health education and services are urgently needed to address knowledge gaps and promote safer behaviors among Myanmar's youth.